Wewowo Local Wisdom in Realizing the Process Sustainable Development - Marini, Heti; Suharto, Didik Gunawan (University of Merdeka Malang, 2022)
Local wisdom is the value and dignity of a society. This greatly affects all aspects of social life. In other words, local wisdom is an aspect in which there are ways of life, behavior, and knowledge about activities carried out by local people for the purpose of maintaining their culture. The purpose of the research is to know the role of local wisdom and to explain its implementation in realizing good governance and creating good community development in public policy. The research uses a qualitative approach, data collection methods through interviews and literature studies. The source of data used in this study is primary data, which was analyzed with a descriptive approach. The results of the study show that the values of local wisdom in Fakfak district as the basis of social and cultural life have values of accountability, transparency, and public participation called Wewowo or adat deliberations. This is a characteristic in the effort to realize good governance in Fakfak district. Some of the empirical manifestations of local wisdom that are embodied in creating good governance are by establishing cooperation between the government and indigenous peoples in order to establish good communication, which will not harm some parties. It is necessary to teach democratic thinking based on ethics and morality to end political taboos in most Fakfak communities.